A Kangaroo Care Pathway for NICU Staff and Families: The Proof Is in the Pouch. (February 2020) - Stadd, Karen; Diehl, Beth; Yenokyan, Gayane; Aucott, Susan W.
Abstract : Background: Kangaroo care (KC) improves bonding and neonatal health outcomes worldwide. However, concerns for patient safety, interrupted workflow, and parent readiness continued to impede KC in a level IV neonatal intensive care unit (NICU). Its current policy did not recommend using more than 1 staff member during patient transfer. In addition, NICU staff and parents lacked skills training and education regarding the feasibility of routine KC. Purpose: A KC pathway was developed and integrated within a multifaceted, champion-based, simulated educational training program for NICU staff and families to promote earlier and more frequent KC by increasing their knowledge and comfort with this practice. Methods: Patient data collected before and after the study determined the frequency, timing, and mode of respiratory support during KC. Pre- and posttest surveys evaluated nurses' knowledge and comfort level with KC. Results: The frequency of KC occurred 2.4 times more after the intervention. The percentage of KC episodes for intubated patients nearly doubled. The posttest survey scores for nursing knowledge and comfort level also markedly improved. Implications for Practice: The KC pathway ameliorated feelings of discomfort by depicting criteria and instructions for safe practice. Multidisciplinary champions were invaluable in assisting the nursing staff with patient transfer during KC. Implications for Research: More dose–response studies are needed to maximize the clinical benefits of KC in developed countries.